The effect of chemical composition on the microstructure and mechanical properties of Ti-Nb-Mo thin films deposited by DCMS on AISI 316L substrate for biomedical applications - Martinez Orozco, Katherine Judith (Universidade Federal de São Carlos, 2025)
The aim of this work is to study the effect of chemical composition on the microstructure and mechanical properties of five titanium β-alloys thin films: Ti74Nb21Mo5, Ti74Nb19M7, Ti72Nb19Mo9, Ti67Nb22Mo11, and Ti71Nb29 (as reference) deposited on AISI 316 L substrates. Films having thicknesses of 671 nm, 573 nm, 841 nm, and 963 nm were deposited by means of direct current magnetron sputtering (DCMS). Microstructural characterization was carried out by scanning electron microscopy (SEM) coupled with energy-dispersive X-ray spectroscopy (EDS), atomic force microscopy (AFM), and grazing incidence X-ray diffraction (GIXRD). The mechanical properties were tested by means of nanoindentation test, residual stress, and potentiodynamic polarization test. In general, homogeneous thin films were obtained with nanometric grain sizes. The films exhibit clusters and pores. Compressive and tensile residual stress were measured, and expressive results correlating with the morphology of the films were found. As more homogeneous the thin film, the higher the compressive stress value. Inverse Hall-Petch relation was observed, explained by the decreasing in the hardness values simultaneously with decreasing in grain size.
O efeito da composição química na microestrutura e nas propriedades mecânicas de filmes finos de Ti-Nb-Mo depositados por DCMS em substrato AISI 316L para aplicações biomédicas
Keywords: Pulverização magneto-catódica de corrente direta; Filmes finos; Recobrimentos; Corrosão; Propriedades mecânicas; Ligas Ti-Nb-Mo; Ligas biomedicas; Módulo elástico; Nanoindentação; Tensão residual; GIXRD; Direct current magnetron sputtering; Thin-films; Coatings; Corrosion; Mechanical properties; Ti-Nb-Mo alloys; Biomedical alloys; Elastic modulus; Nanoindentation; Residual stress; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA